INTERAKSI DAN IMPLEMENTASI TERINTEGRASI DARI PENDIDIKAN, PROFESI KEGURUAN DAN KEILMUAN SAINS DALAM PEMAHAMAN BELAJAR SISWA SMP: APA PENGERTIAN LISTRIK DAN MAGNET? - Elim, Hendry Izaac (Universitas Pattimura, 2023)
This work shows an implementation of teaching assistant for natural science module in junior high school (SMP) particularly on electricity and magnetism by using an integrated interaction and implementation from education system, teacher profession, and scientific knowledge in improving SMP students understanding. The first step was to prepare a correct concept of electricity and magnetism via a simple understanding. Secondly, it was the process to approach schools which were the most possible to accept the treatment and benefits. Finally, the series of transformation process of preparation of educational tools as well as teaching style with enjoyable procedure based on local wisdom knowledge were applied. Our results exhibit a promising response from students, class teachers and school principle especially in the quality content of module supported by the attractive simple experimental tools and teaching method with advanced simple knowledge treatment. Therefore, this study suggests a more preparation on more experimental tools and measurement devices to reach the whole students in the classroom effectively